Dry spell sequences in south coastal Andhra - SUBRAMANIAM , AR; RAO, PSANJEEVA (MAUSAM, 1989)
Agricultural planning as well as many operations depend considerably on the success of dry and over wet spells. A first order Markov chain model has been, utilized to study the initial, and conditional probabilities of weekly rainfall, In terms of dry and wet spells during 1954-1984 at four locations In south coastal Andhra Pradesh The patterns of dry weeks show considerable spatial and temporal variations. The information is useful to agricultural planners in determining the suitable crop or variety for a particular location and in adopting the appropriate agricultural practices.